Die arabische Version der "Vita Dioscori" - Moawad, Samuel (Patrologia orientalis, 2016)
"Dioscorus of Alexandria (444-454) is one of the most important patriarchs in the history of the Coptic Church. The information about his life found in the Coptic and Copto-Arabic literature is based on his Vita that is handed down in Syriac, Karshuni, Arabic, and Coptic fragments. By studying the unedited Arabic version, which is preserved in two manuscripts, it can be seen that it was translated from a Coptic original. However, not all the remaining Sahidic fragments have parallels in the Arabic version. Therefore, it is to be assumed that there was more than one Coptic version and every Coptic version developed independently from the others. The various versions of the Vita Dioscori have the same framework despite the differences between them. The events that are found in only one version and do not appear in the others are later adoptions from other sources. The Vita Dioscori is not mere a hagiographical or even a historical work. It presents above all the reception of Chalcedon among the Copts and the process of creating a Coptic self-identity based on affirming the legitimacy of the Coptic patriarchs as successors of the great Church Fathers. The Vita Dioscori belongs to a corpus of Coptic and Copto-Arabic literature that treats the theological questions in a way that can be understood by the simple Copts in the medieval period. The Arabic version of the Vita includes editorial remarks that are evidence of a liturgical use of this work, presumably on the feast of Dioscorus on the seventh of Tūt according to the Coptic calendar. The Vita is also full of miracles, visions, and prophecies that are used as evidence for the correctness of Coptic orthodoxy compared to Chalcedonian dogma. Therefore, the Vita Dioscori is an ideal model for Coptic literature after Chalcedon and a good example for how the Copts wrote their own Church history."--Publisher's website